(3QHjY GdCHQGQ hfUhU GdCNHGQs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3GdHGH GdSJhf ai PcQ aVd GdcJGHI hGdcJGH GdCaGVd GdgGOi MdGd SMQgG HMQGe SMQ HGHd s
(3BNQgG (B:s
(3CMeO Hf jMji KYdH (B: (3fGdg Mee TOjO ai BNQ CjGeg s
(3HChdgG Jedc jYhO Edi SfI (B1031 (3g`s
(3agQS ddCHhGH hHBNQ UaMGJgG JYbjHIs
(3fSNI YGTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B12 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B832s
Keywords: (3GdCOHs